The myriad roles of Miro in the nervous system: axonal transport of mitochondria and beyond - Lee, Kyu-Sun; Lu, Bingwei (Frontiers in Cellular Neuroscience, 2014)
Mitochondrial rho GTPase (Miro) is a mitochondrial outer membrane protein containing two GTPase domains and two helix-loop-helix Ca2+-binding domains called EF hands. Pioneering genetic studies in Drosophila first revealed a key function of Miro in regulating the axonal transport of mitochondria, during which Miro forms a multi-protein transport complex with Milton and Kinesin heavy chain (KHC) to link trafficking mitochondria with the microtubule cytoskeleton. Recent studies showed that through binding to the EF hands of Miro and causing conformational changes of Miro and alteration of protein-protein interactions within the transport complex, Ca2+ can alter the engagement of mitochondria with the microtubule (MT)/kinesin network, offering one mechanism to match mitochondrial distribution with neuronal activity. Despite the importance of the Miro/Milton/Kinesin complex in regulating mitochondrial transport in metazoans, not all components of the transport complex are conserved in lower organisms, and transport-independent functions of Miro are emerging. Here we review the diverse functions of the evolutionarily conserved Miro proteins that are relevant to the development, maintenance, and functioning of the nervous system and discuss the potential contribution of Miro dysfunction to the pathogenesis of diseases of the nervous system.